Are we there yet? The rigorousness of impact evaluations of nutrition-sensitive agricultural interventions - Meister, Will (International Food Policy Research Institute, 2018)
Several literature reviews have questioned the rigorousness of impact evaluations of nutrition-sensitive agriculture interventions. To understand how their rigorousness could be improved, this study seeks to establish a high-level overview of what rigorousness is, why it has not been realized, and how it could be improved through the use of randomized controlled trials (RCTs), long-term impacts and sustainability, and cost-benefit/cost-effectiveness analyses. To look further into these topics, the author interviewed a judgment sample of individuals from the agriculture-nutrition community. An understanding of rigorousness was derived from the interviews and literature, and was applied to biofortification studies connected to HarvestPlus. Issues related to funding, planning, time, knowledge, and intervention design were identified with regards to RCTs, long-term impacts and sustainability, and cost-benefit/cost-effectiveness analyses. Despite the arguments and difficulties with these three factors, the research community seems to be moving in the direction of greater rigor, as evidenced by some of the most recent research. Specifically, the impact evaluations of biofortification programs provide evidence that implementing more rigorous impact evaluations is possible. Given this movement, there is an opportunity to take a more standardized approach to impact evaluations of nutrition-sensitive agriculture interventions, using the weaknesses identified in the reviews to form the evaluation criteria.